Dinamika Sastera Arab Era Dinasti Umawi Faktor Penyebab Perkembangan Dan Karakteristiknya - Iwan Iwan; Ratu Bilqis (AL-MUFASSIR, 2021)
This paper is intended to study Arabic literature in the era of the Umayyad dynasty. In this paper, the method used is library research, where the author collects data from various literature sources that are relevant to the object of study. These data were then studied using a qualitative descriptive analysis method. The author also uses a historical approach to understand the history that describes the development of Arabic literature in the era of the Umayyad dynasty. The results showed that in the era of the Umayyad dynasty literary development was influenced by several aspects, including the emergence of several political sects and sects in religion which resulted in "feud" between writers (poets) in defense of the beliefs of their groups. In addition, literature during the Umayyad dynasty also functioned in various interests of people's lives at that time